Majene Earthquake: Humanitarian AID Integration System - T Fidowaty; D Amtinannsiafitri; R Rizki; S P Lugina; Maulidina Aisyah (Peneliti.net, 2021)
One area that has the potential for an earthquake is West Sulawesi. When an earthquake occurs, the West Sulawesi government will arrange disaster aid distribution through the Regional Disaster Management Agency (BPBD). This research aims at designing an information system to help the management of aid supplies in West Sulawesi. We used a descriptive method in this research. The qualitative approach was also used in this study to obtain the data. The results show that the difficulty faced by BPBD Majene is in communication between various parties involved in disaster management and recording disaster data. It is due to the complex conditions of the Majene earthquake and difficult coordination. So that in developing this information system is expected to provide easy access by users. In conclusion, with this information system, they can share information by the access rights in the information system.